2006
DOI: 10.1002/pssb.200565425
|View full text |Cite
|
Sign up to set email alerts
|

The dominant shallow 0.225 eV acceptor in GaN

Abstract: We have studied the optical signatures of the Mg acceptor in GaN, using samples that are doped with Mg during MOCVD growth. In order to reduce the defect density in the material and thus achieve narrow linewidths in optical spectra we have used thick HVPE grown GaN layers as templates in the MOCVD growth. The photoluminescence (PL) spectra show two acceptor-related bound exciton peaks at 3.466 eV and 3.455 eV respectively. In the lower photon energy range the 3.27 eV emission with its LO-phonon replicas is dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…There are also two separate acceptor bound excitons present in Mg-doped GaN as shown in Fig. 6b [41]. The identity of the ABE1 acceptor always present in Mg-doped GaN (and dominant in PL spectra) is not known at present.…”
Section: Gan Band Structure Excitons Donors and Acceptormentioning
confidence: 95%
See 1 more Smart Citation
“…There are also two separate acceptor bound excitons present in Mg-doped GaN as shown in Fig. 6b [41]. The identity of the ABE1 acceptor always present in Mg-doped GaN (and dominant in PL spectra) is not known at present.…”
Section: Gan Band Structure Excitons Donors and Acceptormentioning
confidence: 95%
“…A broad background PL band peaking at about 3.1 eV could possibly be the signature of the Mg acceptor (Fig. 6a) [41]. There are also two separate acceptor bound excitons present in Mg-doped GaN as shown in Fig.…”
Section: Gan Band Structure Excitons Donors and Acceptormentioning
confidence: 97%
“…For low Mg doping levels, the relation between the ABE1 peak at 3.466 eV and the 3.27 eV DAP peak (with accompanying LO phonon replicas at lower energies) has been established in the literature. 2,3 For Mg doping at concentrations [Mg] < 10 18 cm À3 these are the only acceptor related PL features in this energy range, and therefore have to be assigned to the substitutional Mg acceptor.…”
Section: B the Dap Spectrum At 327 Evmentioning
confidence: 99%
“…1. These PL signatures for Mg-related acceptors were established only in recent years, [2][3][4] with the ABE1 peak at 3.466 eV in unstrained GaN at 2 K and the corresponding DAP peaking at about 3.27 eV. The latter PL emission was studied in detail already four decades ago 5,6 and established as a DAP emission, but the connection with the Mg acceptor was not definitely known at the time.…”
mentioning
confidence: 99%
“…The second acceptor A2 is associated with ABE2 at ϳ3.453 eV and with a broad band at ϳ3.1 eV. It was suggested that A2 is related to Mg, 7 while A1 has been recently assigned to the shallow C N acceptor.…”
mentioning
confidence: 99%